2016
DOI: 10.1055/s-0042-109263
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of a HTR2B Stop Codon on Glucagon Homeostasis and Glucose Excursion in Non-Diabetic Men

Abstract: Limited data are available about the role of the serotonin 2B (5-HT2B) receptor in the function of human islets. This study aimed to test whether the 5-HT2B receptor contributes to glucose, insulin, and glucagon homeostasis in humans, utilizing a hereditary loss-of-function gene mutation in the receptor, which causes a 50% reduction in the production of the receptor protein in heterozygotes. This clinical study enrolled participants recruited by newspaper advertisements and from mental status examinations. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The regression lines crossed approximately at the testosterone level 27 nmol/L in our sample, which left 10% of the total sample above this pivotal point. Although our results are preliminary and correlative, the results suggest that the effect of testosterone on energy metabolism may partly be dependent of serotonergic mechanisms similar to the relationship between serotonin and insulin-related metabolism (Bennet et al, 2016;Tikkanen et al, 2016). Our results may describe a biochemical physiologic mechanism as the sample was homogeneous and likely exhibited only small variance in behavior.…”
Section: Tablementioning
confidence: 58%
See 1 more Smart Citation
“…The regression lines crossed approximately at the testosterone level 27 nmol/L in our sample, which left 10% of the total sample above this pivotal point. Although our results are preliminary and correlative, the results suggest that the effect of testosterone on energy metabolism may partly be dependent of serotonergic mechanisms similar to the relationship between serotonin and insulin-related metabolism (Bennet et al, 2016;Tikkanen et al, 2016). Our results may describe a biochemical physiologic mechanism as the sample was homogeneous and likely exhibited only small variance in behavior.…”
Section: Tablementioning
confidence: 58%
“…Indeed, preliminary evidence that was mostly obtained from animal study settings suggest that serotonin (5-HT) is involved in the control of islet function and links to insulin resistance (IR) (Bennet et al, 2015;Saunders et al, 2014). Moreover, some studies imply that functional silencing of the serotonin 2B (5-HT2B) receptor may have protective effects on risk for IR and type 2 diabetes (T2D) because the function of the receptor seems to alter islet function and glucose homeostasis (Bennet et al, 2016;Kim et al, 2010Kim et al, , 2015Tikkanen et al, 2016;Yamada et al, 1998). However, the role of the G q -coupled serotonin 5-HT2B receptor in human somatic health is poorly characterized, but in psychiatric research studies the 5-HT2B receptor has been recently shown to exert the following tangible effects on human behavior and psychiatric symptoms: increased impulsive behavior, alcoholrelated problem-behavior, emotional dysregulation, mood disorders, and anxiety (Bevilacqua et al, 2010;Tikkanen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%